Librarian job description / Nur Liyana Abdul Halil and Fiona Ravia Anak Asing - Abdul Halil, Nur Liyana; Asing, Fiona Ravia (Faculty of Information Management, 2014)
According to The Free Dictionary, librarian is define as a person who is a specialist in library work. Without librarians, there is no library because librarians' jobs to fulfil the needs of patrons. They organize each of the materials in libraries by arranging it according to the subject of the materials and provide ways on how to search the materials that patrons want in a quick time. By providing ways how to search materials in an easy way, librarian creates a system call Online Public Access Catalog (OPAC) to help patrons save their time in searching the materials that they want. Here, the librarian job's descriptions are divided into four categories which includes a roles of the librarian, job activities of librarian, librarian job duties, responsibilities and skill of librarian.